2014
DOI: 10.1016/j.anorl.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines (short version) of the French Oto-Rhino-Laryngology – Head and Neck Surgery Society (SFORL) for the management of post-tonsillectomy pain in adults

Abstract: Guidelines on the management of post-tonsillectomy pain in adults were drawn up and graded, based on the levels of evidence of selected articles and on work group consensus. The guidelines stress the importance of patient information and seek to harmonize practice, reduce the risk of postoperative complications and above all improve control of post-tonsillectomy pain in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
6
0
2
Order By: Relevance
“…Thus, most guidelines have been modified. Indeed, Swedish [4] and French [5] guidelines recommend NSAIDs as a first line treatment after tonsillectomy. Similar to NSAIDs, dexamethasone was once incriminated as increasing postoperative bleeding [162].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, most guidelines have been modified. Indeed, Swedish [4] and French [5] guidelines recommend NSAIDs as a first line treatment after tonsillectomy. Similar to NSAIDs, dexamethasone was once incriminated as increasing postoperative bleeding [162].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ideal regimen providing adequate analgesia with few side‐effects after tonsillectomy remains to be defined. Guidelines on pain management after tonsillectomy have previously been published [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The present study suggests that many patients do not receive adequate or underdosed pain management after tonsillectomy. Several high-quality clinical practice guidelines based on results of controlled clinical trials for post-tonsillectomy pain management have been published for children and adults [ 4 , 28 30 ]. They all recommend maintaining adequate analgesia, especially on the first postoperative days.…”
Section: Discussionmentioning
confidence: 99%
“…It concluded that instructions given by otolaryngologists varied significantly from clinic to clinic and within centers from surgeon to surgeon. 15…”
mentioning
confidence: 99%